The Effect of a Model Based on the Hatagogia in the Achievement of Students of the Department of Family Education and Artistic Professions in the Subject of Handicrafts (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
As to start with the target first which means:- The current research aims to identify: The effect of a model based on Hatagogia in theachievement of students of the Department of Family Education and Artistic Professions in thesubject of handicrafts.The SampleThe sample of the research was determined for the students of the fourth stage of the morningstudy of the school year, which numbered (21) male and female students. The researcher chosethe random method by (10) students to represent the control group in which the students studyhandicrafts in the usual way (lecture and discussion), (11) students to represent the groupExperimental, whose students are exposed to the independent variable (a model based on theHatagogia) when teaching the subject of handicrafts.ResultsThe results of the research resulted in the superiority of the students of the experimental groupwho studied according to a model based on the Hatagogia, over the students of the control groupwho studied according to the usual method in the collection of handicrafts.ConclusionsThe researcher concluded the superiority of the experimental group in the post-test, after theywere exposed to the Hatagoga-based educational model prepared by the researcher, whichincludes a set of frameworks with several skills, and these skills explain to the learner the stepsin a simplified manner according to the requirements of their needs.